Geographic Trends in the Ophthalmology Residency Match: Influence of Program and Applicant Characteristics - Cohen, Samuel A.; Pershing, Suzann (Journal of Academic Ophthalmology, 2022)
Introduction The ophthalmology residency match remains competitive. Several prior studies have examined various factors that contribute to a successful match into an ophthalmology residency program; however, the role of geographic location in the ophthalmology residency match process is unclear. The purpose of our study was to evaluate geographic trends in the ophthalmology residency match and to determine whether geographic trends vary based on program level factors such as program rank or funding source and/or applicant factors such as year of training, gender, and medical degree earned. Specifically, we assessed associations with residents training at the residency program affiliated with their medical school and/or within the same geographic region as their medical school, using data obtained through publicly available sources and residency program surveys.Methods We used the American Medical Association's Fellowship and Residency Electronic Interactive Database database to identify accredited ophthalmology residency programs. Residency program Web sites and email inquiries were used to collect demographic and geographic information for residents in the graduating classes of 2021 to 2023. Statistical analysis included χ2 testing and multivariate logistic regression.Results In total, 1,378 residents were included from 110 ophthalmology residency programs and 218 medical schools. Residents who matched at the residency program affiliated with their medical school (18%) were evenly distributed among the Midwest, Northeast, South, and West regions (p = 0.2236). Residency programs in the West (31.7%) matched fewer regional medical students compared with programs in the South (61.2%), Midwest (57.4%), and Northeast (58.4%) (p < 0.0001). Attending a publicly funded medical school was associated with higher odds of matching into a regional residency program (odds ratio [OR], 1.45; 95% confidence interval [CI], 1.10–1.90; p = 0.0001) and attending a privately funded medical school was associated with higher odds of matching into a top-ranked residency program (OR, 1.53, 95% CI, 1.34–1.82; p = 0.0002).Conclusions The majority of current ophthalmology residents trained at programs in the same geographic region as their medical schools, with nearly 20% of residents training at their medical school-affiliated program. Geographic differences in match results were observed based on resident gender, medical school characteristics, and residency program region.
Keywords: geographic; trends; match; residency; ophthalmology